Coping mechanisms among Lebanese first-time college students - Doumit, Rita (2012)
Background: Newly admitted college students are subject to a massive input of stresses which require successful and ever-changing coping strategies. An expanding body of literature suggests that inadequate responses to coping with stress in adolescents of college age contributes to a range of psychosocial problems, including poor academic performance, anxiety, depression, mental distress and eating disorders. Those problems may be further exacerbated for adolescents who live in countries plagued by the uncertainties of war and violence. Significance: The concept of coping is of particular interest in Lebanon given the socio-cultural context in which Lebanese youth pursuit their education and social activities. Methods: A descriptive correlational cross-sectional design was used to explore the relationships of stress, uncertainty, resilience, religiosity, socioeconomic status, social support to coping and well-being in Lebanese newly admitted college students. The Seiffge-Krenke’s Stress, Coping and Outcomes Model (1995) was used as the conceptual framework for this descriptive cross-sectional correlational study. A convenient study sample of 293 newly admitted college students were recruited at the Lebanese American University on the Beirut campus. Data was gathered from self-reported questionnaires. Results: Results demonstrated that Lebanese first-time college students used a combination of internal, active and withdrawal coping strategies as anticipated. Strategies xiv used varied with the type of situation. A greater proportion of overall strategies used included active and internal coping strategies which were focused on resolving the issue or problem. Stress (r= -.547, p < .01) had the highest correlation with well-being followed by social support (r= .377, p < .01), resilience (r = .366, p < .01), uncertainty (r= -.353, p < .01), withdrawal coping (r = -.243, p < .01), and gender (p < .01) as a controlling variable. When all those factors were combined together, six variables in addition to gender accounted for significant increments of variance in the level of wellbeing. These six variables included stress related to self, resilience, uncertainty, social support, religiosity, withdrawal coping and gender. As scores on resilience, social support and being male increased, the well-being of Lebanese first-time College students also increased. As the usage of withdrawal coping strategies, being exposed to stress related to self and uncertainty increased, the well-being of Lebanese first-time college students decreased. The final regression model accounted for 54% of the variance in well-being level (52.7% adjusted) (p < .001). The result of the mediation analysis showed that coping did not mediate the relationship between stress and well-being. Implications for Nursing Practice and Research: The results of this study will provide a better understanding of factors that are predictive of decreased well-being in Lebanese first-time college students and will be valuable in developing culturally sensitive intervention of stress and coping management program with a surveillance system and a systematic planning and evaluation procedure to respond to emerging and changing students’ needs at the Lebanese American University.